PENGARUH CREDIBILITY DAN ATTRACTIVENESS ENDORSER TERHADAP PROSES PEMILIHAN POLITEKNIK LP3I JAKARTA SEBAGAI TEMPAT KULIAH - D Purnomo (JURNAL LENTERA BISNIS, 2018)
AbstractMany Polytechnics, as vocational education providers offer education services even by providing guaranteed employment before graduating from college with attractive promotional programs, even by cutting celebrities. One side of the government has educated the public to continue their education on vocational education, but on the other hand, the number of Polytechnic enthusiasts remains much smaller than other forms of higher education. This study aims to determine the responses of respondents to the credibility and attractiveness endorsers of the Polytechnic LP3I Jakarta (PLJ), the PLJ selection process as a place of study, as well as the influence of PLJ credibility and attractiveness towards the PLJ selection process as a place of study. This research method uses descriptive verification method, with a regression analysis tool with SPSS 16. The results show that the credibility and attractiveness of PLJ endorsers as well as the PLJ selection process as a lecture place are responded well at a good level by respondents, besides that there is an influence from the credibility and attractiveness of PLJ endorsers to the PLJ selection process as a place of study.Keywords: Credibility, Attractiveness, Endorser, Selection Process.